(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s ((3GHf TGg eMehO edG eMeO HGSe s)
(3ChdgG (B:s
(3gdjL CUaQ efRhY Gdfhi , hRf SHYI OQGge , hjRjO ai GdJbhjI ef GdSbehfjG hGdEfWGcjG GdLjOI hRf fUa OGfb fGaY s
(3BNQgG (B:s
(3hjfaY ef dSY GdghGe , UaI bQU GdCaGYi JDNP CaGYi aJjI GdSf EfGK ZjQ PchQ , GdaQb Hjf GdPchQ s
(3Hg UaMGJ cKjQI HjVGAs
(3ef fSNI KGefIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
Keywords: (3GdWHs